Fine Needle Aspiration Biopsy in Oral Mass Lesion - Agoeng Tjahajani; Titiek Setyawati; Rosnah Zain; Nurshaline Nurshaline (Faculty of Dentistry, Universitas Indonesia, 2013)
Background: In many developing countries, like Indonesia, most patients with oral mass lesions, i.e. infection, inflammation, even cancer came to the hospital at late stages of the disease. Some of them afraid of endure suffering a killer disease, either after a biopsy or even should undergo an operation. Fine needle aspiration (FNA) biopsy is a technique rarely used to diagnose oral ad oropharyngeal lesion. This technique seems promise a convenienve, painless, accurate, safe, and easy to use to help patients and surgeons, and have been demonstrated repeatedly. Objectives: This case report emphasized many advantages of FNA biopsy to examine oral mass lesions and its metastasis to lymph node. Materials and Methods: Under a local anesthesia, incisional biopsy and FNA biopsy were done on four cases of oral mass lesions. All samples were prepared for microscopic examination with Hematoxylin-Eosin (HE) staining and with Diff-Quick or Papaniculaou staining. Results: Incisional biopsy shoed features of malignancy as the same as FNA biopsy. There were bigger cells with high ratio between cells and nucleus, hyperchromatic nucleoli, and mitotic cells that refers to Squamous cell carcinoma. FNA biopsy from the nearest lymph node showed clumps atypia cells, prominent nuceloli, nuclear hyperchromatic and pleomorphism. Conclusion: FNA biopsy could well diagnose on oral mass lesions and the adjacent lymph node. FNA biopsy has many advantages particularly its convenience, painless, ease to use, cost effectiveness, and accuracy. DOI: 10.14693/jdi.v16i2.92